2019
DOI: 10.1002/ece3.5443
|View full text |Cite
|
Sign up to set email alerts
|

Structure from motion photogrammetry in ecology: Does the choice of software matter?

Abstract: Image‐based modeling, and more precisely, Structure from Motion (SfM) and Multi‐View Stereo (MVS), is emerging as a flexible, self‐service, remote sensing tool for generating fine‐grained digital surface models (DSMs) in the Earth sciences and ecology. However, drone‐based SfM + MVS applications have developed at a rapid pace over the past decade and there are now many software options available for data processing. Consequently, understanding of reproducibility issues caused by variations in software choice a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 65 publications
2
25
0
Order By: Relevance
“…Both have drawn attention from the scientific community, but with ODM being the newer option, the focus has primarily been on its development and initial quality testing (3,4,53,54). MicMac’s maturity has allowed for a deeper scrutiny (55,56), has been utilised as the primary SfM-MVS option in geomorphological studies (57) and has been shown to be comparable to both Pix4D and Agisoft Photoscan (Metashape) within a low sward grassland study (58).…”
Section: Open Source Sfm-mvsmentioning
confidence: 99%
See 4 more Smart Citations
“…Both have drawn attention from the scientific community, but with ODM being the newer option, the focus has primarily been on its development and initial quality testing (3,4,53,54). MicMac’s maturity has allowed for a deeper scrutiny (55,56), has been utilised as the primary SfM-MVS option in geomorphological studies (57) and has been shown to be comparable to both Pix4D and Agisoft Photoscan (Metashape) within a low sward grassland study (58).…”
Section: Open Source Sfm-mvsmentioning
confidence: 99%
“…NodeMicMac is still in its infancy but now provides a user two different SfM-MVS processing options from within the one, WebODM interface. Also, as the original version of MicMac can have a steep learning curve (58), this provides an easier, more user-friendly option for deploying MicMac.…”
Section: Open Source Sfm-mvsmentioning
confidence: 99%
See 3 more Smart Citations